Understanding the multiculturalism values through social media among Indonesian youths - Tuti Budirahayu; Marhaeni M. Wijayanti; Katon Baskoro (Faculty of Social and Political Science, Universitas Airlangga, 2018)
The diversity of Indonesian people can be a problem when they do not have a sense of brotherhood based on the diversity of religion, culture, language and ethnic groups. Understanding diversity is known by young people through various media outlets. This study aims to understand the level of the knowledge of youths concerning the values of pluralism and multiculturalism. This study also intends to find out whether social media influence the knowledge and their understanding of pluralism and multiculturalism. However, the demographic bonus could be a burden for the countries involved, particularly when the generation lacks competitiveness. This can even cause the disintegration of this nation. This study was a quantitative research study conducted using the survey method. The respondents consisted of 400 young people in high school or the equivalent. The study was conducted in three cities in East Java, namely Surabaya, Pasuruan, and Kediri. The samples were taken using the multi-stage cluster random sampling method. The data was obtained through structured questionnaires and processed using SPPS for Windows 16. The results can be explained as follows; even though more than fifty percent of the youths in this study claimed to have never heard or known of the term “pluralism” and “multiculturalism”, their level of comprehension of pluralism and multiculturalism values was good enough. This was influenced by the information that they got through social media. The values that are understood more by the youths through social media in this study tend to be more orientated to pluralism values than multiculturalism. The most understood pluralism values are plurality and diversity. This is in line with their assessment of the role and quality of the information available on social media, which tends to contain pluralism values rather than multiculturalism values.